The Role of Cysteine Peptidases in Hematopoietic Stem Cell Differentiation and Modulation of Immune System Function - Perišić Nanut, Milica; Pečar Fonović, Urša; Jakoš, Tanja; Kos, Janko (Frontiers in Immunology, 2021)
Cysteine cathepsins are primarily involved in the degradation and recycling of proteins in endo-lysosomal compartments but are also gaining recognition as pivotal proteolytic contributors to various immune functions. Through their extracellular proteolytic activities within the hematopoietic stem cell niche, they are involved in progenitor cell mobilization and differentiation. Cysteine cathepsins, such as cathepsins L and S contribute to antigen-induced adaptive immunity through major histocompatibility complex class II antigen presentation whereas cathepsin X regulates T-cell migration. By regulating toll-like receptor signaling and cytokine secretion cysteine cathepsins activate innate immune cells and affect their functional differentiation. Cathepsins C and H are expressed in cytotoxic T lymphocytes and natural killer cells and are involved in processing of pro-granzymes into proteolytically active forms. Cytoplasmic activities of cathepsins B and L contribute to the maintenance of homeostasis of the adaptive immune response by regulating cell death of T and B lymphocytes. The expression pattern, localization, and activity of cysteine cathepsins is tightly connected to their function in immune cells. Furthermore, cysteine cathepsins together with their endogenous inhibitors, serve as mediators in the interplay between cancer and immune cells that results in immune cell anergy. The aim of the present article is to review the mechanisms of dysregulation of cysteine cathepsins and their inhibitors in relation to immune dysfunction to address new possibilities for regulation of their function